Human Cdc14B promotes progression through mitosis by dephosphorylating Cdc25 and regulating Cdk1/cyclin B activity. - Indra Tumurbaatar; Onur Cizmecioglu; Ingrid Hoffmann; Ingrid Grummt; Renate Voit (PLoS ONE, 2011)
Entry into and progression through mitosis depends on phosphorylation and dephosphorylation of key substrates. In yeast, the nucleolar phosphatase Cdc14 is pivotal for exit from mitosis counteracting Cdk1-dependent phosphorylations. Whether hCdc14B, the human homolog of yeast Cdc14, plays a similar function in mitosis is not yet known. Here we show that hCdc14B serves a critical role in regulating progression through mitosis, which is distinct from hCdc14A. Unscheduled overexpression of hCdc14B delays activation of two master regulators of mitosis, Cdc25 and Cdk1, and slows down entry into mitosis. Depletion of hCdc14B by RNAi prevents timely inactivation of Cdk1/cyclin B and dephosphorylation of Cdc25, leading to severe mitotic defects, such as delay of metaphase/anaphase transition, lagging chromosomes, multipolar spindles and binucleation. The results demonstrate that hCdc14B-dependent modulation of Cdc25 phosphatase and Cdk1/cyclin B activity is tightly linked to correct chromosome segregation and bipolar spindle formation, processes that are required for proper progression through mitosis and maintenance of genomic stability.